Disease incidence and genetic variability of economically important grapevine viruses in Nova Scotia. Issue 4 (1st October 2020) - Poojari, Sudarsana; Moreau, Debra L.; Kahl, Dieter; Ritchie, Mark; Ali, Shawkat; Úrbez-Torres, José Ramon
Abstract: Several virus diseases cause damage to Vitis vinifera L., but information on their incidence and impact on hybrid cultivars is scarce, particularly under cool-climate conditions. In Nova Scotia (NS), the wine industry is based predominantly on interspecific hybrid cultivars. To understand the occurrence of major grapevine viruses in NS, surveys were conducted in 2016, 2017 and 2018. A total of 965 composite five-vine samples, collected from 35 hybrids and 18 V. vinifera vineyard blocks, were tested for grapevine leafroll-associated virus 1 (GLRaV-1), GLRaV-2, GLRaV-3 and GLRaV-4, grapevine fanleaf virus (GFLV), grapevine red blotch virus (GRBV) and grapevine Pinot gris virus (GPGV) by PCR/RT-PCR. Overall, 3.4% of the samples were positive for GLRaV-1, 22.8% for GLRaV-3, 0.9% for GFLV, 4.6% for GRBV and 3.2% for GPGV. None of the 575 samples collected in 2016 and 2017 tested positive for GLRaV-2 or GLRaV-4. Mixed infections by more than one virus occurred in 3% of the composite samples. Of 671 hybrid and 294 V. vinifera samples tested, 38.3% and 27.6% were positive for at least one of the viruses (GLRaV-1, −3, GFLV, GRBV and GPGV), respectively. Phylogenetic analysis of GLRaV-1, −3, GFLV and GPGV revealed the presence of global variants. Complete genome characterization and phylogenetic analysis of nine GRBV isolates grouped three into clade I and six into clade II, indicating the presence of two variants. These findings, along with preliminary reports of insect vectors, establish the first epidemiological framework of the major viral diseases in NS, highlighting the need for long-term management strategies.